PENGEMBANGAN BAHAN AJAR BERBASIS PRAKTIKUM SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN MAHASISWA CALON GURU FISIKA - murniati murniati (Universitas Sriwijaya, 2019)
Learning colleges prepare students to enter employment well, have very specific skills or expertise according to market needs, or instead have general transferable skills needed by almost all government or private institutions (Rosyada, 2016). In order to produce graduates who are ready to compete, learning in class not only provides knowledge but also the skills needed according to demands. Improvements in learning are the responsibility of lecturers and efforts to improve them can be done through research. Lecturers as lecturers should improve the quality of learning in class by doing variations in lectures. The results showed that the application of the cooperative group investigation model in mechanics courses that used valid and practical teaching materials as development products could improve student learning outcomes (Murniati, 2017). Based on the description above, the writer feels it is necessary to develop teaching materials based on practicum as an effort to improve the professionalism of students as prospective physics teachers, because the demands in the field expect that a physics teacher not only masters theory but is also skilled in conducting learning in the laboratory. The method in developing practicum-based teaching materials refers to the development of Rowntree with the Tessmer evaluation which consists of the planning, development and evaluation stages. Based on the results of expert validation and comments that the developed teaching materials are valid, from the results of one-to-one and small group trials, students comment that teaching-based teaching materials can make it easier to understand the concepts and from questionnaire data analysis results obtained that the teaching materials are already practical .